PENGEMBANGAN BUKU KONSEP MATEMATIKA BERBASIS PROBLEM-BASED LEARNING (PBL) PADA POKOK BAHASAN PELUANG - Vahmala, Iis; Syafri, Fatrima Santri (Universitas Islam Nusantara, 2026)
This study aims to develop a mathematics concept book based on Problem Based Learning (PBL) on the subject of probability and to test its validity, practicality, and effectiveness. The research method uses the Plomp development model, which includes the stages of initial investigation, prototype development, and evaluation. The results of expert validation show that the mathematics concept book is highly valid, with a percentage of 86.67% for the material, 93.33% for the media, and 90% for the language. The practicality test on 11 students resulted in a score of 72.72%, which indicates that the concept book is practical. The effectiveness of the module was evident from the improvement in learning outcomes with an average N-Gain score of 0.4174 in the moderate category, and the t-test showed a significant improvement (t = 8.92; p < 0.05). Thus, the PBL-based module was declared valid, practical, and effective in improving the understanding of probability concepts and supporting more contextual learning.